PENGEMBANGAN MULTIMEDIA DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK PEROLEHAN BELAJAR KONSEP PUISI DI KELAS X SMA - Yulianto, Dedi; Aswandi, Aswandi; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractInstructional media allows you to: 1) excite learning; 2) liken the experience; 3) improve the experience; 4) create the perception of the same. One of the media that is currently widely used by teachers is a computer media. This study used a qualitative approach with methods of research and development. Sources of data in this study were students of class X SMAN 4 Ketapang. Results of the study are: (1) the basic pattern design relevant learning in poetry writing material designed using the inquiry strategy, deductive methods and techniques of learning in the form of question and answer; (2) prototype design relevant learning designed using interactive media that contain text, images, sound and video; (3) The relevant storyboard profile developed based on basic competencies and learning objectives and learning materials poetry; (4) Display interactive media using Adobe Flash Player is ideal to use in learning poetry because it makes students more interested and able to master the subject matter well; (5) There is an increased average acquisition learning outcomes Class X SMAN 4 Ketapang after using interactive media Adobe Flash Player which ranged between 10% - 12% of each class. Keywords: multimedia, learning acquisition, the concept of writing poetry